Failure properties and microstructure of healthy and aneurysmatic human thoracic aortas subjected to uniaxial extension with a focus on the media. (November 2019) - Sherifova, Selda; Sommer, Gerhard; Viertler, Christian; Regitnig, Peter; Caranasos, Thomas; Smith, Margaret Anne; Griffith, Boyce E.; Ogden, Ray W.; Holzapfel, Gerhard A.
Graphical abstract: Abstract: Current clinical practice for aneurysmatic interventions is often based on the maximum diameter of the vessel and/or on the growth rate, although rupture can occur at any diameter and growth rate, leading to fatality. For 27 medial samples obtained from 12 non-aneurysmatic (control) and 9 aneurysmatic human descending thoracic aortas we examined: the mechanical responses up to rupture using uniaxial extension tests of circumferential and longitudinal specimens; the structure of these tissues using second-harmonic imaging and histology, in particular, the content proportions of collagen, elastic fibers and smooth muscle cells in the media. It was found that the mean failure stresses were higher in the circumferential directions (Control-C 1474 kPa; Aneurysmatic-C 1446 kPa), than in the longitudinal directions (Aneurysmatic-L 735 kPa; Control-L 579 kPa). This trend was the opposite to that observed for the mean collagen fiber directions measured from the loading axis (Control-L > Aneurysmatic-L > Aneurysmatic-C > Control-C), thus suggesting that the trend in the failure stress can in part be attributed to the collagen architecture. The difference in the mean values of the out-of-plane dispersion in the radial/longitudinal plane between the control and aneurysmatic groups was significant. The difference in the mean values of the mean fiber angle from the circumferential direction was also significantly different between the two groups. Most specimens showed delamination zones near the ruptured region in addition to ruptured collagen and elastic fibers. This study provides a basis for further studies on the microstructure and the uniaxial failure properties of (aneurysmatic) arterial walls towards realistic modeling and prediction of tissue failure. Statement of Significance: A data set relating uniaxial failure properties to the microstructure of non-aneurysmatic and aneurysmatic human thoracic aortic medias under uniaxial extension tests is presented for the first time. It was found that the mean failure stresses were higher in the circumferential directions, than in the longitudinal directions. The general trend for the failure stresses was Control-C > Aneurysmatic-C > Aneurysmatic-L > Control-L, which was the opposite of that observed for the mean collagen fiber direction relative to the loading axis (Control-L > Aneurysmatic-L > Aneurysmatic-C > Control-C) suggesting that the trend in the failure stress can in part be attributed to the collagen architecture. This study provides a first step towards more realistic modeling and prediction of tissue failure.